Personality Traits and Anxiety Related to Artificial Intelligence among Educators in Serbia: The Mediating Role of Resilience, Work Locus of Control, and Burnout Syndrome - Davidović Rakić, Jelena I.; Popović, Emilija U.; Pavićević, Miljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
In the context of rapid technological advancement, particularly in the field of education, the increasing use of artificial intelligence (AI) raises questions about how individual psychological characteristics influence the experience and regulation of AI-related anxiety among teaching staff. The aim of this study was to examine whether resilience, work locus of control, and burnout syndrome mediate the relationship between personality traits and levels of AI-related anxiety among educators in the Republic of Serbia. The research was conducted on a sample of 324 teachers from primary and secondary schools. The following instruments were used: the Ten-Item Personality Inventory (TIPI–10) to assess personality dimensions, the Brief Resilience Scale (BRS) to measure resilience, Spector’s Work Locus of Control Scale (SWLC), the Copenhagen Burnout Inventory (CBI) to assess burnout syndrome, and the Artificial Intelligence Anxiety Scale (AIA). The results indicate that personality traits have a weak direct effect on AI-related anxiety. Neuroticism contributes to higher levels of AI-related anxiety indirectly, through external work locus of control and burnout syndrome. Conscientiousness and resilience act as protective factors by reducing burnout syndrome and strengthening internal work locus of control, which in turn predict lower AI-related anxiety. These findings highlight the importance of strengthening teachers’ internal psychological capacities in the process of adapting to the demands of a shifting educational system.